The Effect of Muhawarah Method on Speaking Skills of Arabic Language Education Students at UINSI Samarinda - Diah Aulia Ulfah; Ahmad Fadhel Syakir Hidayat; Miftahul Khair; Badrun Nisyam; Mar’ie Muhamad; Evi Nursaudah Apriani (El-Syaker : Samarinda International Journal of Language Studies, 2024)
The implication of the Muhawarah Method on the Speaking Skills of Arabic Language Education Students at Sultan Aji Muhammad Idris State Islamic University Samarinda is a deep discussion. Therefore, the purpose of this study is to see the extent of the influence of the muhawarah method on student speaking skills. The method used in this study is a quantitative method with a sampling technique, namely saturated samples, using research instruments, namely questionnaires, interviews, and documentation, where the entire population is sampled as many as 28 students of the Arabic Language Education study program 1 class of 2020 who study using the Muhawarah Method. The results showed that learning Maharah Al-Kalam by applying the Muhawarah Method went well, attracted students' enthusiasm in learning, and was not so difficult to follow.  Based on the results of the T test, the value of t_hitung is 9.648> t_table with a level of 0.025 (2.056). So the decision in this study Ha is accepted and Ho is rejected. So it is concluded that there is an influence on the Muhawarah Method on Maharah Al-Kalam for PBA students in the Class of 2020 UINSI Samarinda. And based on the results of the coefficient of determination test, the result obtained is 0.782, which means that the effect of the Muhawarah Method on Maharah Al-Kalam is 78.2%.